The Effect of the Local-R Learning Model on Interest in Learning Islamic Religious Education at State Middle School 28 Bandar Lampung - Suci Safitri; Muhammad Indra Saputra; Deden Makbulloh (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
Learning interest is a crucial factor in achieving educational goals, particularly in Islamic Religious Education (PAI) subjects, which emphasize not only cognitive aspects but also affective and spiritual dimensions. This study aims to examine the effect of the LOK-R learning model (Literacy, Orientation, Collaboration, Reflection) on students' learning interest, focusing on indicators such as attention to teachers, intrinsic motivation, learning perseverance, active participation, and their connection to spiritual values. The study employs a quantitative approach using a quasi-experimental design with a post-test-only control group and simple random sampling. The implementation of the LOK-R model fosters a more interactive and enjoyable learning environment. In conclusion, the LOK-R model shows potential as an innovative approach to enhance learning interest; however, its effectiveness should be further validated by expanding the indicators and refining the research instruments.